Improving Junior High School Students' Vocabulary Mastery through Wordwall.net Media - Faradila, Nandatul; Lapita, Yuni; Fadhli, Muhammad (TRIADIK, 2023)
Abstract This research attempted to investigate the effectiveness of using Wordwall.net media to improve junior high school students' vocabulary mastery. This research carried out classroom action research (CAR). Thirty students of class VIII.E at SMPN 7 Kota Bengkulu in the academic year of 2022/2023 were the research subjects. The instruments used were vocabulary test, observation checklist, and note. The results showed the improvement in students' vocabulary test that was proven in the percentage of students who passed the Minimum Mastery Criterion (KKM) from the pre-cycle to cycle 2. The improvement of classroom situations during the teaching-learning process also occurred in terms of students' attention, activeness, and confidence in learning English. Thus, wordwall.net is a potential medium to teach English vocabulary.